2014
DOI: 10.1080/10236244.2014.894349
|View full text |Cite
|
Sign up to set email alerts
|

Immune responses ofLitopenaeus vannameito thermal stress: a comparative study of shrimp in freshwater and seawater conditions

Abstract: The effects of hypothermal (22-16°C) and hyperthermal (22-28°C) stress on the immune system responses of the shrimp Litopenaeus vannamei cultured in either freshwater or seawater were measured and compared. The following immune system indicators were measured for comparison: total hemocyte count (THC), activity of phenoloxidase (PO), nitric oxide synthase (NOS), superoxidase (SOD), and malondialdehyde (MDA) content. Thermal stress significantly decreased THC in both freshwater and seawater shrimp within 6-12 h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…Like other invertebrates, nonspecific immunity is shrimp's main defence against pathogens (Jia et al, 2014;Li & Xiang, 2013). LZM, ALP and NOS are identified as important immune indices of shrimp.…”
Section: Discussionmentioning
confidence: 99%
“…Like other invertebrates, nonspecific immunity is shrimp's main defence against pathogens (Jia et al, 2014;Li & Xiang, 2013). LZM, ALP and NOS are identified as important immune indices of shrimp.…”
Section: Discussionmentioning
confidence: 99%
“…As ectotherms, C. gigas physiology and response to pathogens are controlled by temperature and intertidal oysters could thus benefit from an "environmental fever" during emersion. It could resemble the "behavioral fever" of ectothermic vertebrates, such as zebrafish moving to warmer environments to amplify their innate immunity against viral disease (Boltaña et al, 2013;Jia et al, 2014). Indeed, in plants and invertebrates, the innate immune system is shaped by the environment and lifestyle (diet and microenvironment) (Melillo et al, 2018), the heat-stress amplifying immune training, as demonstrated in shrimp (Jia et al, 2014).…”
Section: Can Bathymetry Cause Environmental Fever?mentioning
confidence: 99%
“…It could resemble the "behavioral fever" of ectothermic vertebrates, such as zebrafish moving to warmer environments to amplify their innate immunity against viral disease (Boltaña et al, 2013;Jia et al, 2014). Indeed, in plants and invertebrates, the innate immune system is shaped by the environment and lifestyle (diet and microenvironment) (Melillo et al, 2018), the heat-stress amplifying immune training, as demonstrated in shrimp (Jia et al, 2014). Such immune training can even confer an immunological memory, also called immune priming, resulting in a faster and more effective response to stress (Melillo et al, 2018;Netea et al, 2020).…”
Section: Can Bathymetry Cause Environmental Fever?mentioning
confidence: 99%